Prenatal development of uterus in the Surti buffalo - BAISHYA, G; VYAS, K N (The Indian Journal of Animal Sciences, 2013)
Uteri from Surti buffalo normal foetuses (62) were studied at different phases of prenatal life, ranging from 62 to 305 days (5.5 to 93.0 em CR). The first evidence of formation of uterus was noticed in 67 days (6.1 cm CR) embryos through the caudal fusion of the 2 Mullerian duct. The epithelium of the developing uterus was of pseudostratified ciliated columnar type in 75 days (8.5 cm CR) foetuses. The uterine lining oiepithelium became folded at 116 days (15.0 cm CR)of foctal age. A median septum separated the future uteri in 85 days (9.5 cm CR). A progressive condensation and differentiation of mesenchymal tissues and a serosal covering around the uterine portion .was observed in 85 days. Endometrium. myometrium and perimetrium, were clearly distinguishable in 130 days (20.5 cm CR) and resembled that of adult uterus in 174 days of gestational age. Endometrial caruncles first appeared in 130 days which were lined by pseudostratified to simple columnar epithelium. Uterine glands made their first appearance in 191 days (35.0 cm CR) of foetal age. The uterus mainly demonstrateti a reticular and collagenous connective tissue mesh work with a fibrous perimetrium at later foetal age. It is therefore concluded that the amount of collagenous fibres in general, increased ,vith advancing gestational age in the uterus of buffalo.